Avaliação de um sistema de realidade virtual para reabilitação do membro superior de pacientes pós AVC - Soares, Nayron Medeiros (2016)
Stroke is a common neurological disorder, classified as the third death cause and mean cause of long-term disability worldwide. The majority of survivors has different levels of impairments. During the technological advancement, virtual reality has been widely used for care and rehabilitation on stroke. We proposed to evaluate the experience and effectiveness of a virtual reality system to promote the rehabilitation of the upper limb on post-stroke. This is a experimental, descriptive and analytical research with a quantitative and qualitative approach. This study was developed at Neuroscience and Behavior Laboratory (LaNeC), located in the Physical Therapy Department of State University of Paraíba. The sample was non-probabilistic for accessibility, composed by three post-stroke patients. Besides the game for training of participants, was used the following instruments for evaluation: Clinical Evaluation and patient experience Report, Mini-Mental State Examination, Box and blocks, Eye-Hand Coordination of Melo test and Transcranial Magnetic Stimulator. Data was expressed descriptively, on average, standard deviations and percentages. To verify the data normality was used Shapiro-Wilk test. To compare both groups was used parametric t-test. The inferential analysis was fulfilled by the statistic program GraphPad Prism version 6.0. In all analyzes was considered the significance level of 5% (p <0.05) and 95% confidence interval. This study was approved by the Ethics Committee of the State University of Paraíba with protocol nº51638015.0.0000.5187. Our study shown that the Leap Motion Controller is a new tool of high level. The therapy proposed with the game was well-received by the patients. The short-term intensive use provided a decrease of the cortical motor threshold of the studied patients (p=0,0430). However, it suggests that new studies be conducted with randomized methodological designs and controlled with bigger sample of post-stroke patients.